Механохімія як перспективна методологія зеленої хімії для промислових каталізаторів - Zazhigalov, V.A.; Wieczorek-Ciurowa, K.; Sachuk, O.V.; Bacherikova, I.V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2021)
In this survey we have assessed how mechanochemistry techniques comply with the aims of Green Chemistry to minimise the use of environmentally damaging reactants and unwanted by-products. In the publications the preparation of vanadium- phosphorus oxides as industrial catalysts for maleic anhydride production from n-butane and perspective catalysts of phthalic anhydride manufacture by direct n-pentane oxidation were analyzed. It is shown that mechanochemical activation and synthesis reduces the amount of harmful waste used in the production of the catalyst and increases its effectiveness. Improvement of a catalyst’s properties, help limit production of harmful emissions such as carbon oxides and hydrocarbons. It was established that mechanochemical treatment can by successfully used in the process of industrial vanadium-phosphorus oxide catalysts modification or in the process of introduction in its composition of additives which lead to increase of activity and selectivity of hydrocarbons oxidation. The possibility of the mechanochemistry use in the vanadium-titanium oxide catalysts preparation which are the base catalysts in industrial phthalic anhydride production from o-xylene was determined. It was established that mechanochemical treatment of the vanadium and titanium oxides mixture permits to delete the nitrogen oxides emission in atmosphere and prepared catalysts demonstrate the same phthalic anhydride yield but at low reraction temperature. Catalysts, manufactured by mechanochemical treatment (on the base of molybdenum oxide), provide new techniques for producing compounds as exemplified by the direct oxidation of benzene to form phenol which can replace industrial two-step process from cumene or proposed process of benzene oxidation by N2O. Mechanochemistry treatment could produce catalysts which eliminated the need to use highly toxic nitrogen oxides as reducing agents. The article describes activating Cu-Ce-O catalysts which reduce the temperature of the process for removing carbon monoxide from exhaust gases and as a method for purifying hydrogen u sed in fuel cells. Finally, there is a description of mechanochemically treated catalysts, containing metals and supported on stainless steel supports which are used to remove aromatic hydrocarbons from water sewers.